RECOGNITION OF THE REED INSTRUMENT SOUNDS BY USING STATISTICAL NEURAL NETWORKS - Bolat, Bulent (YILDIZ TECHNICAL UNIV, 2005)
In this paper, reed instrument sounds were recognised by using statistical neural networks. Linear prediction coefficients were used as features. Three different statistical neural network structures were used for this task. The best structure and it's parameters were determined.
Keywords: Sound recognition; computational auditory scene analysis; statistical neural networks; PNN; GRNN; RBF; Engineering